Nonlinear behavior and ultimate torsional capacity of cantilever steel I-girders with corrugated webs - Bhat, Javed Ahmad (Journal of Structural Engineering, 2024)
Steel girders with corrugated webs are gaining popularity over simple flat-web girders for their benefits, particularly in shear and torsion. Corrugations in the web enhance torsional stability and reduce the need for stiffeners. This study parametrically investigated the influence of geometric characteristics of steel I-girder flange, web, and corrugation folds on the nonlinear torsional behavior of corrugated-web steel girders (CWGs). The Finite Element (FE) modeling used in the study is validated against documented experimental results from the literature for five different loading cases applied on CWGs. In total, 35 nonlinear FE models with fixed-free (i.e., cantilever) boundary conditions were generated using various combinations of geometry parameters. The results showed that the web slenderness ratio and corrugation angle significantly influence the nonlinear torsional capacity of cantilever CWGs. Moreover, the flange width, thickness and girder span are other significant parameters affecting the torsion capacity in CWGs.